GUGATAN GANTI RUGI DALAM PERKARA PENIPUAN MELALUI PERADILAN PERDATA - Muhklis Suhendro (Res Justitia : Jurnal Ilmu Hukum, 2023)
Today there are many cases of fraud that result in losses by some people. However, the judge also cannot order the perpetrators of the crime of fraud to make compensation, considering that this is the realm of civil justice. In addition, based on the Law on Judicial Powers, judges are prohibited from deciding cases outside the demands. The public's lack of understanding about each judiciary in Indonesia causes misunderstandings to occur. Often people assume that they cannot get compensation for the criminal act of fraud committed by the suspect. However, if viewed in depth, the community can actually get the compensation by filing a lawsuit through the civil court. The legal basis used to file a lawsuit against fraud perpetrators is not article 378 of the Criminal Code or the Information and Electronic Technology Law, but article 1365 of the Civil Code (hereinafter referred to as the Civil Code). The following is the content of Article 1365 of the Civil Code. To file a civil lawsuit in a fraud case, the victim should file a criminal lawsuit first. Then the results of criminal court decisions are used as written evidence in civil lawsuits. Thus, the victim is not difficult to prove